PELATIHAN BERBASIS TEKNOLOGI INFORMASI UNTUK MEMBANGUN APLIKASI MOBIL - Edwar Ali; Triyani Arita Fitri; Koko Harianto; Hamdani Hamdani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
SMK N 6 Pekanbaru is one of the vocational schools located in remote areas of Pekanbaru City. In this school there is a Software Engineering (RPL) major that has XII grade students, more than 30 people. The service carried out at this school aims to equip students with technical knowledge of building mobile based application programs. The theme of this service does not overlap with the learning material they get at school. The number of participants is limited to 19 people. The location of the service was carried out at the computer laboratory of SMK N 6 Pekanbaru. The executor of this community service consists of 4 lecturers from STMIK Amik Riau who are accompanied by 2 senior students. The duration of implementation is 2 days. After the implementation of the community service activities, students are expected to have an understanding of the technical aspects of building mobile applications to be able to make applications simply.